Potential kidney protection with liraglutide and semaglutide: Exploratory mediation analysis. Issue 9 (1st June 2021) - Mann, Johannes F. E.; Buse, John B.; Idorn, Thomas; Leiter, Lawrence A.; Pratley, Richard E.; Rasmussen, Søren; Vilsbøll, Tina; Wolthers, Benjamin; Perkovic, Vlado
Abstract: Aims: To investigate whether effects on chronic kidney disease risk factors could explain the apparent reduction in kidney outcomes (composite of macroalbuminuria, doubling of serum creatinine, renal replacement therapy, or renal death), primarily driven by changes in albuminuria, after treatment with the glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) liraglutide and semaglutide in patients with type 2 diabetes in the LEADER and SUSTAIN 6 trials. Materials and Methods: We evaluated the mediation effect of glycated haemoglobin (HbA1c), systolic blood pressure (BP), and body weight on the kidney effects of GLP‐1RAs. Diastolic BP, haemoglobin, heart rate, low‐density lipoprotein and total cholesterol, and white blood cell count were also investigated. The mediation effect was estimated by the novel Vansteelandt statistical method. Subgroups with estimated glomerular filtration rate (eGFR) <60 and ≥60 mL/min/1.73 m 2 were examined in LEADER. Results: We observed that HbA1c mediated 25% (95% confidence interval [CI] −7.1; 67.3) and 26% (95% CI noncalculable), and systolic BP 9% (95% CI 2.8; 22.7) and 22% (95% CI noncalculable) of kidney effects of GLP‐1RAs in LEADER and SUSTAIN 6, respectively. Small or no mediation was observed for the other parameters; for example, body weight mediated 9% (95% CI −7.9; 35.5) in the former and did not mediate effects in the latter study. Mediation by HbA1c was greater in patients with eGFR ≥60 mL/min/1.73 m 2 (57%) versus those with eGFR <60 mL/min/1.73 m 2 (no mediation). Conclusions: Our results suggest that HbA1c and systolic BP may moderately mediate kidney benefits of liraglutide and semaglutide, with all other variables having a small to no effect. Potential kidney benefits may be driven by other mediators or potentially by direct mechanisms.